Intelligent metasurface system for automatic tracking of moving targets and wireless communications based on computer vision - Weihan Li; Qian Ma; Che Liu; Yunfeng Zhang; Xianning Wu; Jiawei Wang; Shizhao Gao; Tianshuo Qiu; Tonghao Liu; Qiang Xiao; Jiaxuan Wei; Ting Ting Gu; et al. (Nature Communications, 2023)
The authors present an intelligent metasurface system that uses a target detection algorithm combined with a depth camera, to automatically detect the position of moving targets and achieve real-time wireless communications. The system can operate for multiple targets in limited ambient light, outdoor and other realistic environments.